Influence of Ethylene Inhibitors and Ethrel on Production of Protocorm Like Bodies in Orchid-Dendrobium 'Sonia' - G V S Saiprasad; P Raghuveer (Journal of Horticultural Sciences, 2007)
To increase the efficiency of production of protocorm like bodies, ethylene inhibitors like silver nitrate, salicylic acid and cobalt chloride at three concentrations, viz., 2, 5 and 20 μM and ethrel at 0.7, 1.4 and 14.0 μM were tested, by supplementing MS basal with BAP 4.44 μM. The explant used was fractionated protocorm like bodies (plb). Ethylene and methane gases evolved by the explant in the culture container were measured at 20 and 40 days after inoculation (DAI). Among various ethylene inhibitors tested, the maximum number of plb's were produced in media containing silver nitrate (5 μM), cobalt chloride (2 μM) and salicylic acid (20 μM). All ethrel treatments produced succulent, vitrified and deformed plb's. No ethylene evolution was observed in any of the ethylene inhibitor treatments. Only in ethrel treatments was evolution of ethylene observed. Methane evolution was observed in all the ethylene inhibitor treatments. Absolute amounts of methane evolved could not be related to the observed plb production. However, when the evolution of methane was more than 1 nano mole g-1 FW h-1, poor plb production was observed.